THE STUDENTS' PUBLIC SPEAKING ANXIETY IN ACADEMIC PRESENTATION (A CASE STUDY AT THE SIXTH SEMESTER STUDENTS OF ENGLISH LANGUAGE EDUCATION UIN MATARAM) - Fira Santun Rabbiani (Journal of English Education and Literature, 2024)
The primary aim of this research is to delve into the roots of public speaking anxiety among sixth-semester English language education students at Mataram State Islamic University, Indonesia, and to elucidate the strategies adopted by these students in mitigating anxiety during academic presentations. Employing a descriptive qualitative research approach, this study amalgamates both primary and secondary data sources. Data collection comprises interviews, observations, and documentation analysis. The analysis method encompasses data reduction, presentation, and inference drawing, further fortified by a triangulation data credibility test. The findings revealed that students grappling with presentation anxiety often exhibit visibly tense facial expressions, struggle to establish sustained eye contact with their audience, overly rely on written materials or electronic aids, and manifest physical symptoms of anxiety such as excessive hand movements. These manifestations collectively underscore the multifaceted nature of public speaking anxiety among students and point towards potential areas of intervention and support to enhance their presentation skills and alleviate anxiety levels.